La Educación y la Teoría del Reconocimiento: entrevista a Axel Honneth - Hernàndez I Dobon, Francesc J.; Herzog, Benno; Martins, Maurício Rebelo (Educação & Realidade, 2016)
Entrevista a Axel Honneth.